Students' misconceptions in solving problem of fractions among Form 2 students in SMK Seksyen 9, Shah Alam, Selangor / Noorsazlinda Sahaifuding - Sahaifuding, Noorsazlinda (2017)
The purpose of this research was to determine performance of students in solving problem of fractions and to investigate the misconceptions of students in learning fractions among Form 2 students in Sekolah Menengah Kebangsaan Seksyen 9, Shah Alam. A total of 90 students that came from different classes which were 2 KRK 3, 2 HARMONI and 2 BUDI were participated in this study. The instrument used to assess students’ performance of students in topic of fractions. The Shapiro- Wilk test was used to check normality of distribution. Since the distribution was not normal, whenever applicable, all test used will be for non- normal distribution. The overall students’ performance in solving problem of fractions based on the analysis was average. The students’ performance in solving problem of fractions based on level of mastery was weak. There was no significant difference between students’ performance in solving problem of fractions and genders. There was no significant difference between students’ performance in solving problem of fractions and classes. From the qualitative data, there were common misconceptions already done by the students. There was significant different between students’ level of knowledge toward fractions and classes. Overall, the students can master and less did the misconceptions in topic of fractions if they were be careful in solving problem on it.